2018
DOI: 10.3390/md16100351
|View full text |Cite
|
Sign up to set email alerts
|

The Cocktail Effect of BMP-2 and TGF-β1 Loaded in Visible Light-Cured Glycol Chitosan Hydrogels for the Enhancement of Bone Formation in a Rat Tibial Defect Model

Abstract: Bone tissue engineering scaffolds offer the merits of minimal invasion as well as localized and controlled biomolecule release to targeted sites. In this study, we prepared injectable hydrogel systems based on visible light-cured glycol chitosan (GC) hydrogels containing bone morphogenetic protein-2 (BMP-2) and/or transforming growth factor-beta1 (TGF-β1) as scaffolds for bone formation in vitro and in vivo. The hydrogels were characterized by storage modulus, scanning electron microscopy (SEM) and swelling ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…However, thermo-sensitive hydrogels that are widely utilized as injectable systems might cause systemic toxicity because a high dosage of anticancer drugs is released during the initial burst [17]. Because of these problems, in our previous studies, a visible light-cured GC hydrogel system was designed and applied to cancer therapy [6,7,8]. GC has a water solubility because inter- and intramolecular hydrogen bonding was broken by introducing the glycol group to the hydroxyl group of water-insoluble chitosan [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, thermo-sensitive hydrogels that are widely utilized as injectable systems might cause systemic toxicity because a high dosage of anticancer drugs is released during the initial burst [17]. Because of these problems, in our previous studies, a visible light-cured GC hydrogel system was designed and applied to cancer therapy [6,7,8]. GC has a water solubility because inter- and intramolecular hydrogen bonding was broken by introducing the glycol group to the hydroxyl group of water-insoluble chitosan [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In this hydrogel system, the initial burst of anticancer drugs was found to be affected by controlling the crosslinking density with the visible light irradiation time [6,7,8]. Thus, a visible light-cured hydrogel system can control the initial burst and has an injectable function [6,7,8]. In the present study, we investigated the potential of visible light-cured GC hydrogel containing PTX for OC therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still unclear the molecular signalings that modulates the effects of downhill running exercise on osteoblastic differentiation in growing mice. It has been reported that the TGF-β/Smad pathway plays an important role in regulating osteoblast formation [16,22]; but the changes and functions of TGF-β/Smad pathway in response to downhill running has not been determined in growing mice yet. Our study showed that the molecular expression of TGF-β, Smad2, Smad3, and Smad4 were significantly increased in exercising mice, and the downstream regulatory gene Runx2 was also enhanced markedly.…”
Section: Discussionmentioning
confidence: 99%
“…However, inflammatory response, lipogenesis, difficulty in dose control, and long-term retention of supplemental growth factors in the injured area may affect its function and even be harmful to the human body, requiring the hydrogel to act as a slow-release agent [ 40 , 41 ]. Yoon et al [ 42 ] prepared an injectable glycol chitosan hydrogel system containing BMP-2 and transforming growth factor-β1 (TGF-1) for in vitro and in vivo scaffolds of bone formation, which can be released continuously for 30 days to increase bone volume and bone density at bone defect sites.…”
Section: Hydrogels As Biomedical Materials For Btementioning
confidence: 99%